Growing the Character Values to Students Through Application of Realistic Mathematics Education (RME) in the Social Arithmetic Learning - Suyitno, Amin (Jurusan Matematika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Sema, 2015)
AbstractEducating students at the Basic Education level is not only demanded that the students are clever, but there are also other demand which no less important that is to educate so that students have a good character value. EducatingÂ the students to have a good character value is started from home, school, and community. In school, educating character to students is not only the duty of teachers of Religion or Civics class, but also the duty of all teachers, including the teachers in Mathematics. Math teacher does not need to hold special time for educating of character, but it can be integrated into any material taught, and also in different application of learning models. This paper examines how the efforts of mathematics teacher in educating of character to the students of Basic Education, especially in Junior High School through the application of Realistic Mathematics Education (RME) on the material of Social Arithmetic. Through presenting of the material of Social Arithmetic by RME learning model, students can be given a character education through the attitude of honesty, tolerance, discipline, cooperation, creative, independent, democratic, curiosity, love of peace, social care, responsibility, and so on. In conclusion, educational character values to students can be done by mathematics teacher through a variety of materials.Â One of them Â through presenting of the material of Social Arithmetic by RME learning model.